PENGARUH PENDEKATAN SAINS, TECHNOLOGY, ENGINEERING, MATHEMATICS (STEM) BERBANTUAN MEDIA SCRATCH TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR - Sulistia Janika; Puji Rahayu; Nurdiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Scientific literacy skills are one of the important skills to develop in science learning because they can help students have the ability to solve problems by utilizing science and technology. Scientific literacy skills must be trained from an early age from elementary school level. However, previous research shows that elementary school students' scientific literacy abilities are still low. The application of the STEM approach is one type of learning that can improve the scientific literacy skills of elementary school students. This is the basis for carrying out this research. The aims of this research are: 1) To determine the effect of the science technology, engineering, mathematics (STEM) approach assisted by scratch on the scientific literacy abilities of elementary school students, 2) To determine the increase in scientific literacy abilities of elementary school students who receive learning using the STEM approach assisted by scratch media. better than students who receive learning with a scientific approach. The research method used in this research is Quasi Experimental Design in the form of Non-equivalent Control Group Design in science and technology learning on energy transformation material. The instrument used is a scientific literacy ability test. The conclusions that can be obtained from this research are: 1) There is an influence of applying the scratch-assisted STEM approach on students' scientific literacy abilities by 48.2%, 2) There is an increase in scientific literacy abilities who receive learning using the scratch-assisted STEM approach better than students who get learning with a scientific approach.